The Effect Of Fibre Layering Pattern In Resisting Bending Loads Of Natural Fibre-Based Hybrid Composite Materials - Muhamad Shahirul, Mat Jusoh; Mohd Yazid, Yahya; Nur Izan Syahriah, Hussein (EDP Sciences, 2016)
The effect of fibre layering pattern and hybridization on the flexural properties of composite hybrid laminates between natural fibres of basalt, jute and flax with synthetic fibre of E-glass reinforced epoxy have been investigated experimentally. Results showed that the effect fibre layering pattern was highly significant on the flexural strength and modulus, which were strongly dependent on the hybrid configuration between sandwich-like (SL) and intercalation (IC) sequence of fibre layers. In addition, specific modulus based on the variation densities of the hybrid laminates was used to discover the best combination either basalt, jute or flax with E-glass exhibits superior properties concerning on the strength to weight-ratio. Generally, SL sequence of glass/basalt exhibited superior strength and stiffness compared with glass/jute and glass/flax in resisting bending loads. In terms of hybridization effect, glass/jute was found to be the best combination with E-glass compared to the rest of natural fibres investigated in the present study. Hence, the proper stacking sequences and material selection are among predominant factors that influence on mechanical properties and very crucial in designing composite hybrid system to meet the desired requirements.